Programmed Locomotion of an Active Gel Driven by Spiral Waves. (11th March 2020) - Ren, Lin; Wang, Liyuan; Gao, Qingyu; Teng, Rui; Xu, Ziyang; Wang, Jing; Pan, Changwei; Epstein, Irving R.
Abstract: Active media that host spiral waves can display complex modes of locomotion driven by the dynamics of those waves. We use a model of a photosensitive stimulus‐responsive gel that supports the propagation of spiral chemical waves to study locomotive transition and programmed locomotion. The mode transition between circular and toroidal locomotion results from the onset of spiral tip meandering that arises via a secondary Hopf bifurcation as the level of illumination is increased. This dynamic instability of the system introduces a second circular locomotion with a small diameter caused by tip meandering. The original circular locomotion with large diameter is driven by the push‐pull asymmetry of the wavefront and waveback of the simple spiral waves initiated at one corner of gel. By harnessing this mode transition of the gel locomotion via coded illumination, we design programmable pathways of nature‐inspired angular locomotion of the gel. Abstract : Laufen und drehen : Durch den Wechsel zwischen Dunkelheit und Belichtung kann ein Übergang zwischen einer annähernd linearen („laufen") und toroidalen („drehen") Fortbewegung realisiert werden. Eine solche Mischbewegung findet sich häufig bei biologischen Aktivitäten wie z. B. Larventaxis.